Загальні принципи права як сутнісні його характеристики - Балаклицький, I.I. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Право как явление социальной действительности характеризуется множествами существенными чертами и необходимыми признаками. Среди них важнейшая роль принадлежит принципам права. В статье особое внимание уделено раскрытию сущности права, учитывая систему, виды, иерархию и значимость его принципов. The Right as the phenomenon of the social validity is characterized by sets essential features and necessary attributes. Among them the major role belongs to principles of the right. In to become the special attention to disclosing of essence of the right will be attached, considering system, kinds, hierarchy and the importance of its principles.